Clinical efficacy evaluation of TiRobot-assisted minimally invasive treatment for calcaneal fractures based on enhanced recovery after surgery principles - Yonghong, Dai; Shi, Hong; Shiheng, Wang; Yanhui, Zeng; Kuangyang, Yang; Shaoyun, Wang (Frontiers in Surgery, 2025)
BackgroundCalcaneal fractures were the most common hindfoot fractures, with most being intra-articular. Compared to fractures in other locations, calcaneal fractures had poorer prognoses. These fractures significantly reduced patients' quality of life, causing long-term chronic pain and functional impairment. Rapid recovery was crucial for restoring patients' normal life and work abilities. Advances in robotic technology provided a new surgical approach to promote faster rehabilitation for calcaneal fractures.MethodsA retrospective analysis was conducted on the medical records of 20 patients with calcaneal fractures who underwent surgery at Foshan Hospital of Traditional Chinese Medicine from October 2020 to November 2024. Based on surgical methods, patients were divided into the robot-assisted group (10 cases) and the control group (10 cases). The robot-assisted group underwent closed reduction and cannulated screw fixation assisted by TiRobot. The control group received traditional open reduction and plate fixation. No significant differences were found in baseline characteristics between the two groups (P > 0.05), ensuring comparability. Data on incision length, operative time, intraoperative blood loss, hospitalization duration, fracture healing time, calcaneal length, width, height, Böhler angle, Gissane angle after complete healing, internal fixation removal, and complications were recorded and compared. At the final follow-up, VAS scores and AOFAS scores with grading were documented. Statistical analysis was performed using IBM SPSS Statistics 26.0. Continuous variables were assessed for normality using the Shapiro–Wilk test. Normally distributed data were expressed as mean ± standard deviation (x¯±s) and compared using independent samples t-tests. Non-normally distributed data were presented as median (lower quartile, upper quartile) [M (Q1, Q3)] and analyzed with Mann–Whitney U tests. Categorical data were reported as percentages and compared using Fisher's exact test. A two-sided significance level of α = 0.05 was adopted for all statistical tests.ResultsNo statistically significant differences were observed between the two groups in terms of calcaneal length, width, height, Gissane angle, AOFAS score grading, postoperative complications, and the number of patients who opted for internal fixation removal after complete fracture healing (P > 0.05). The operative time in the robotic group was significantly longer than that in the control group, with a statistically significant difference (P < 0.05). The intraoperative blood loss in the robotic group was 17.50 ± 17.68 ml, compared to 45.00 ± 39.79 ml in the control group, indicating that the robotic group had significantly less intraoperative blood loss, with a statistically significant difference (P < 0.05). The incision length in the robotic group was 2.30 ± 0.48 cm, while it was 8.10 ± 1.45 cm in the control group, demonstrating that the robotic group had significantly smaller incision lengths, with a statistically significant difference (P < 0.05). The hospitalization duration in the robotic group was significantly shorter than that in the control group, with a statistically significant difference (P < 0.05). The restoration of Böhler's angle in the robotic group was significantly better than that in the control group, with a statistically significant difference (P < 0.05). The fracture healing time in the robotic group was significantly shorter than that in the control group, with a statistically significant difference (P < 0.05). The VAS score in the robotic group was 0.40 ± 0.70, compared to 2.00 ± 1.56 in the control group, indicating that the robotic group had significantly lower VAS scores, with a statistically significant difference (P < 0.05). The AOFAS score in the robotic group was 94.80 ± 6.21, while it was 85.40 ± 7.99 in the control group, demonstrating that the robotic group had significantly higher AOFAS scores, with a statistically significant difference (P < 0.05).ConclusionCompared to the control group, TiRobot-assisted minimally invasive treatment for calcaneal fractures significantly reduced intraoperative blood loss and incision length, shortened hospitalization duration, better restored calcaneal anatomy, accelerated fracture healing, more effectively alleviated postoperative pain, and promoted early functional recovery.